Desempenho ponderal de bezerros das raças Nelore e cruzados Nelore x Senepol e Nelore x Montana - LEMOS, Evelyn Oliveira; AMORIM, Lidianny dos Santos; OSHIRO, Maurílio Massaharu; Dalton Mendes de (ANAIS DO ENIC, 2025)
-